Dipole coupling effect of holographic fermion in charged dilatonic gravity - Wen, Wen-Yu; Wu, Shang-Yu (My University, 2012)
In this Letter, we study the dipole coupling effect of holographic fermion in a charged dilatonic black hole proposed by Gubser and Rocha (2010) [1]. It is found that the property of Fermi liquid is rigid under perturbation of dipole coupling, and the Fermi momentum is linearly shifted. A gap is dynamically generated as the coupling becomes large enough and the Fermi surface ceases to exist as the bulk dipole coupling further increases. (C) 2012 Elsevier B.V. All rights reserved.